204k views
1 vote
If 8a + 7b + c = 9, what is -6c - 48a - 42b

User Per Ersson
by
5.2k points

2 Answers

2 votes
The correct answer is -54
User Max Kielland
by
5.1k points
3 votes

Answer:

-54

Explanation:

8a + 7b + c = 9

We want -6c, but we have c in the equation so multiply by -6

-6(8a + 7b + c) = 9*-6

-48a -42b -6c = -54

Rearranging the equation

-6c - 48a - 42b = -54

User MiketheCalamity
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.